Differential expression of CCR8 in tumors versus normal tissue allows specific depletion of tumor-infiltrating T regulatory cells by GS-1811, a novel Fc-optimized anti-CCR8 antibody. (31st December 2022) - Weaver, Jessica D.; Stack, Edward C.; Buggé, Joshua A.; Hu, Changyun; McGrath, Lara; Mueller, Amy; Wong, Masie; Klebanov, Boris; Rahman, Tanzila; Kaufman, Rosemary; Fregeau, Christine; Spaulding, Vikki; et al.
ABSTRACT: The presence of T regulatory (Treg) cells in the tumor microenvironment is associated with poor prognosis and resistance to therapies aimed at reactivating anti-tumor immune responses. Therefore, depletion of tumor-infiltrating Tregs is a potential approach to overcome resistance to immunotherapy. However, identifying Treg-specific targets to drive such selective depletion is challenging. CCR8 has recently emerged as one of these potential targets. Here, we describe GS-1811, a novel therapeutic monoclonal antibody that specifically binds to human CCR8 and is designed to selectively deplete tumor-infiltrating Tregs. We validate previous findings showing restricted expression of CCR8 on tumor Tregs, and precisely quantify CCR8 receptor densities on tumor and normal tissue T cell subsets, demonstrating a window for selective depletion of Tregs in the tumor. Importantly, we show that GS-1811 depleting activity is limited to cells expressing CCR8 at levels comparable to tumor-infiltrating Tregs. Targeting CCR8 in mouse tumor models results in robust anti-tumor efficacy, which is dependent on Treg depleting activity, and synergizes with PD-1 inhibition to promote anti-tumor responses in PD-1 resistant models. Our data support clinical development of GS-1811 to target CCR8 in cancer and drive tumor Treg depletion in order to promote anti-tumor immunity.